2011
DOI: 10.4315/0362-028x.jfp-10-483
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Campylobacter, Salmonella, and Escherichia coli Isolated from Retail Grain-Fed Veal Meat from Southern Ontario, Canada

Abstract: This study estimated the prevalence of Salmonella, Campylobacter, and Escherichia coli isolates in fresh retail grain-fed veal obtained in Ontario, Canada. The prevalence and antimicrobial resistance patterns were examined for points of public health significance. Veal samples (n = 528) were collected from February 2003 through May 2004. Twenty-one Salmonella isolates were recovered from 18 (4%) of 438 samples and underwent antimicrobial susceptibility testing. Resistance to one or more antimicrobials was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…The antimicrobial surveillance systems in Canada and the United States report the absence of CIP resistance among E. coli isolates from beef, pork, chicken, or turkey at the retail or abattoir levels (5,17,18). However, fluoroquinolone resistance was also detected in retail grain-fed veal E. coli isolates in a parallel study and has also been isolated in a recent Swiss study of fecal samples from veal calves at slaughter (7,9). CIP is clinically important for the treatment of serious human invasive bacterial gastrointestinal infections in adults, such as salmonellosis and severe campylobacteriosis (24).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The antimicrobial surveillance systems in Canada and the United States report the absence of CIP resistance among E. coli isolates from beef, pork, chicken, or turkey at the retail or abattoir levels (5,17,18). However, fluoroquinolone resistance was also detected in retail grain-fed veal E. coli isolates in a parallel study and has also been isolated in a recent Swiss study of fecal samples from veal calves at slaughter (7,9). CIP is clinically important for the treatment of serious human invasive bacterial gastrointestinal infections in adults, such as salmonellosis and severe campylobacteriosis (24).…”
Section: Discussionmentioning
confidence: 93%
“…In a recent study of retail grain-fed veal in Ontario, isolates of E. coli were recovered from 88% of the meat samples purchased in local grocery stores; 54% of the bacterial isolates were resistant to one or more antimicrobials (7). During that study, a smaller number of milk-fed veal samples were also collected, cultured for E. coli, and analyzed for antimicrobial resistance.…”
mentioning
confidence: 99%
“…Campylobacter jejuni was isolated from 1 of 8 raw beef liver samples but not from 8 pork and 8 beef raw meats in a study conducted in Ontario over a 2-year period (Medeiros et al 2008). Similarly, a low prevalence was found in raw veal meat (1/438) in Ontario (Cook et al 2011), ground beef (1%-12.5%) in Ontario between 2007 and 2009, and pork chops (0%-18%) in Ontario between 2006 and 2009 (Table 6; PHAC 2009b). In addition, a study using carcass swab samples of cattle and hogs stored in coolers at slaughterhouses in Alberta showed a low contamination prevalence for cattle (1.5%) and pig (8.8%) samples (Bohaychuk et al 2011).…”
Section: Raw and Ready-to-eat Meat And Poultrymentioning
confidence: 90%
“…No significant study has been performed yet to evaluate the role of jambul juice on the growth of pathogenic bacteria and beneficial microflora. Our study [26], who reported blueberry juice to inhibit the growth of S. typhimurium, Campylobacter jejuni, L. monocytogenes, and E. coli O157:H7; the study of Puupponen-Pimiä et al [27] who reported that phenolic compounds of berries, especially ellagitannins inhibited the growth of gram negative bacteria like Staphylococcus, Salmonella, and Listeria; and Park et al [28] Moreover, ensuring the safety of the food supply chain has become more difficult due to the resurgence of multidrug resistant strains of foodborne pathogens [31] [32]. Natural antimicrobial agents like jambul juice may be an effective alternative choice against the bacterial pathogens that are resistant to available drugs.…”
Section: Discussionmentioning
confidence: 99%